2014
DOI: 10.1111/1365-2745.12231
|View full text |Cite
|
Sign up to set email alerts
|

Variability in seed cone production and functional response of seed predators to seed cone availability: support for the predator satiation hypothesis

Abstract: Summary1. Mast seeding is a reproductive strategy in some perennial plants defined as synchronous production of large seed crops at irregular intervals. One widely accepted theory to explain this behaviour is the predator satiation hypothesis, which states that the synchronous and variable production of seeds within a population will maximize the probability of seed survival through satiation of seed predators. 2. Although some short-term studies have documented the influence of variable and synchronized produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 53 publications
7
75
0
Order By: Relevance
“…Parallel results at both levels demonstrate the ecological (population level) and evolutionary (individual tree level) benefits of masting in tree species. Finally, our present findings, in combination with previous assessments of this same population (Mooney et al 2011;Linhart et al 2014), indicate that masting behavior has in all likelihood evolved as a response to multiple selective forces, including both pollen limitation and herbivory (Rossi et al 2012).…”
Section: Figsupporting
confidence: 79%
See 1 more Smart Citation
“…Parallel results at both levels demonstrate the ecological (population level) and evolutionary (individual tree level) benefits of masting in tree species. Finally, our present findings, in combination with previous assessments of this same population (Mooney et al 2011;Linhart et al 2014), indicate that masting behavior has in all likelihood evolved as a response to multiple selective forces, including both pollen limitation and herbivory (Rossi et al 2012).…”
Section: Figsupporting
confidence: 79%
“…Most notably, the predator satiation hypothesis states that masting allows escape from local seed predators through herbivore satiation (Janzen 1971, Silvertown 1980. Indeed, an independent analysis based on the same data set used in the present study provides strong support for this hypothesis at both the individual and population levels (Linhart et al 2014). The pollination efficiency and predator satiation hypotheses are based on an economy of scale, where perennial plants benefit from larger and less frequent reproductive efforts instead of more frequent and smaller ones (Norton andKelly 1988, Rossi et al 2012).…”
Section: Figsupporting
confidence: 63%
“…Secondly, synchronous bouts of high cone production, followed by intervening years of low reproduction, reduced seed cone herbivory through predator satiation (Linhart et al . ). Additionally, we found that production of mature seed cones in this population was strongly influenced by spring (May–July) mean temperature 2 years before cone maturation ( T i ‐2 model hereafter) (Mooney, Linhart & Snyder ).…”
Section: Introductionmentioning
confidence: 97%
“…For instance, a 29‐yr study on Pinus ponderosa showed a markedly lower rate of seed predator attack during mast years compared with years of low seed production (Linhart et al. ). Kelly & Sork () conducted a literature review of 570 mast‐seeding data sets, and found that predator‐dispersed plant species had higher CVs than species dispersed by other animals, supporting the predator satiation hypothesis.…”
Section: Introductionmentioning
confidence: 99%